Deltamethrin induced an apoptogenic signalling pathway in murine thymocytes : exploring the molecular mechanism. Issue 12 (12th November 2013) - Kumar, Anoop; Sasmal, D.; Sharma, Neelima
ABSTRACT Deltamethrin (DLM) is a well‐known pyrethroid insecticide; however, the immunotoxic effects of DLM on the mammalian system and its mechanism is still unclear. This study has been designed to first observe the binding affinity of DLM to immune cell receptors and its effects on the immune system. The docking score revealed that DLM has a strong binding affinity towards the CD4 and CD8 receptors. DLM induces apoptosis in murine thymocytes in a concentration‐dependent manner. The ear\ly markers of apoptosis such as enhanced reactive oxygen species (ROS) and caspase‐3 activation are evident as early as 1 h by 25 and 50 μM DLM. Glutathione (GSH) depletion has also been observed at 1 h by 50 μM DLM concentration. In cell‐cycle studies using flow cytometry, the fraction of hypodiploid cells has gradually increased with all the concentrations of DLM at 18 h. The Annexin V binding assay measures the effect of DLM on apoptotic and necrotic cells. The apoptotic cells raised from 18.6% to 35.21% (10–50 μM DLM) at 18 h. N‐acetyl cysteine (NAC) effectively reduced the percentage of apoptotic cells which is increased by DLM. In contrast, buthionine sulfoximine (BSO) caused an elevation in the percentage of apoptotic cells. These results demonstrate that caspase activation, ROS activation and GSH act as critical mediators in a DLM‐induced apoptogenic signalling pathway in murine thymocytes. In the presence of caspase inhibitor, the percentage of apoptotic cells is partially decreased. Thus, there may be the possibility of some other caspase‐independent pathways in DLM‐induced apoptosis. Copyright © 2013 John Wiley & Sons, Ltd.